2017
DOI: 10.1002/hed.24846
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of videofluoroscopic swallow study findings before and after cricopharyngeal myotomy

Abstract: Both symptomatic and objective improvement in swallowing measures occurs after cricopharyngeal myotomy. Pouch remnants and retained barium are seen postoperatively but do not correlate with reported symptoms. Routine follow-up barium studies may be needed to establish a new baseline and allow for comparison if future symptom recurrence occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Although several studies reported the relationship between the EAT-10 score and the presence of OD, only two studies investigated this relationship in HNC patients; of these, neither used FEES to evaluated swallowing. [40][41][42][43][44][45][46][47] Arrese et al enrolled 44 HNC patients and compared the EAT-10 scores with the presence of OD using videofluoroscopie (VFS) examination. 46 OD was determined using the penetration-aspiration scale and the modified barium swallow impairment profile.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies reported the relationship between the EAT-10 score and the presence of OD, only two studies investigated this relationship in HNC patients; of these, neither used FEES to evaluated swallowing. [40][41][42][43][44][45][46][47] Arrese et al enrolled 44 HNC patients and compared the EAT-10 scores with the presence of OD using videofluoroscopie (VFS) examination. 46 OD was determined using the penetration-aspiration scale and the modified barium swallow impairment profile.…”
Section: Discussionmentioning
confidence: 99%
“…19 Patients are placed in a lateral decubitus position, and the operation is performed under conscious sedation or narcosis, freehand, or using various devices (e.g., needle-knife, hook-knife, monopolar forceps). 5,20 This type of procedure is particularly indicated for patients unsuitable for general anesthesia due to comorbidities or for patients who have unfavorable anatomical features or problems concerning the positioning of the Weerda diverticuloscope. Flexible endoscopy for ZD has yet to be standardized, and different cutting techniques can be combined with different accessories depending on physicians' personal experience and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Flexible endoscopic ZD treatment is feasible as well . Patients are placed in a lateral decubitus position, and the operation is performed under conscious sedation or narcosis, freehand, or using various devices (e.g., needle‐knife, hook‐knife, monopolar forceps) . This type of procedure is particularly indicated for patients unsuitable for general anesthesia due to comorbidities or for patients who have unfavorable anatomical features or problems concerning the positioning of the Weerda diverticuloscope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations